Authority of the superior commander in commanding and leading subordinates - Kałużny , Ryszard (Scientific Journal of the Military University of Land Forces, 2024)
The author addresses the problem of the superior’s authority andits importance in commanding subordinates in uniformed services.Based on the analysis of the source literature and his own experi-ences, he defines the concept of authority and interprets its types.In the context of reflections on the subject of authority, he alsodefines the concepts of command and leadership and indicates thepositive consequences of liberating authority but also to the neg-ative implications of authoritarian management of subordinates.